2012
DOI: 10.1016/j.febslet.2012.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Signaling property study of adhesion G‐protein‐coupled receptors

Abstract: a b s t r a c tAdhesion G-protein-coupled receptors (GPCR) are special members of GPCRs with long N-termini containing multiple domains. We overexpressed our collection of receptors together with G-proteins in mammalian cell lines and measured the concentrations of intracellular signaling molecules, such as inositol phosphate and cAMP. Our results show that a subset of tested adhesion GPCRs has constitutive activities and is capable of coupling to a variety of G-proteins. In addition, we have identified a smal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
76
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 90 publications
(84 citation statements)
references
References 16 publications
(24 reference statements)
4
76
0
3
Order By: Relevance
“…Using this approach, ADGRD1 (GPR133) showed a receptor concentrationdependent increase in cAMP levels, which is indicative of Ga s coupling (Bohnekamp and Schoneberg, 2011) and IP 3 levels when using a Ga qi chimera, indicating Ga i coupling . Using a similar approach, coupling to Ga s , Ga q , Ga i/o , or Ga 12/13 proteins was demonstrated for several other Adhesion GPCRs (Gupte et al, 2012;Stephenson et al, 2013). In sum, multiple lines of direct and indirect evidence support the notion that most members of the Adhesion GPCR family can likely mediate signals by activation of G protein cascades.…”
Section: A G Protein-mediated Intracellular Signalingmentioning
confidence: 78%
See 1 more Smart Citation
“…Using this approach, ADGRD1 (GPR133) showed a receptor concentrationdependent increase in cAMP levels, which is indicative of Ga s coupling (Bohnekamp and Schoneberg, 2011) and IP 3 levels when using a Ga qi chimera, indicating Ga i coupling . Using a similar approach, coupling to Ga s , Ga q , Ga i/o , or Ga 12/13 proteins was demonstrated for several other Adhesion GPCRs (Gupte et al, 2012;Stephenson et al, 2013). In sum, multiple lines of direct and indirect evidence support the notion that most members of the Adhesion GPCR family can likely mediate signals by activation of G protein cascades.…”
Section: A G Protein-mediated Intracellular Signalingmentioning
confidence: 78%
“…It has been shown that Adhesion GPCRs with a truncated NTF can be expressed at the cell surface, showing basal activity in cAMP assays (Bohnekamp and Schoneberg, 2011), and such truncated receptors could be used for small molecule screening. Beclomethasone dipropionate was recently identified to specifically induce G protein activation via binding to ADGRG3 (GPR97) (Gupte et al, 2012). The availability of low-molecular-weight substances would likely facilitate approaches to target the wide range of Adhesion GPCRs that are expressed in the brain, a tissue that cannot easily be accessed by peripherally administered antibodies owing to the presence of the blood-brain barrier.…”
Section: Perspectives On Pharmacological Opportunitiesmentioning
confidence: 99%
“…Knockdown and overexpression of G proteins caused a depletion and increase, respectively, of second messenger accumulation (Bohnekamp and Schöneberg, 2011;Liebscher et al, 2014b) (Gupte et al, 2012) and GPR126 (Liebscher et al, 2014b) under basal and stimulated conditions.…”
Section: In Vitro Pharmacology Of Agpcrsmentioning
confidence: 97%
“…Early experiments showed that LPHN1 can be copurified with Ga o (Lelianova et al, 1997), and stimulation with a-latrotoxin, a known LPHN1 ligand, evokes neurotransmitter release in the presence of extracellular calcium in a phospholipase C-dependent manner (Rahman et al, 1999). Other indirect functional evidence came from second messenger assays (Bohnekamp and Schöneberg, 2011;Gupte et al, 2012;Mogha et al, 2013;Liebscher et al, 2014b) and activated downstream components of G protein signaling cascades (Iguchi et al, 2008;Bohnekamp and Schöneberg, 2011;Yang et al, 2011;Ward et al, 2011;Giera et al, 2015).…”
Section: In Vitro Pharmacology Of Agpcrsmentioning
confidence: 99%
See 1 more Smart Citation